Analysis of the effect of H2O content on combustion behaviours of a biogas fuel. (29th January 2020) - Sahin, Murat; Ilbas, Mustafa
Abstract: The present work deals with the biogas in a combustor with regard to its combustion features under differing conditions of H2 0 content and H2 S. The content of water (H2 O) vapour has been changed from 0% to 10% and a CFD code has been employed while implementing numerical investigations. In modelling, a combustion model (the PDF/Mixture Fraction) along with a turbulence model (the k-Ɛ standard turbulence model) has been utilised. This study also deals with the combustion performances of the biogas by the addition of a different quantity of H2 O into the biogas. The Emissions and the flame temperature of the biogas through the combustor apparently seem to be strikingly affected by the changes in H2 O contents. It is interesting to note that the flame temperature zones change their positions and advance to the burner's downstream. The rise in flame temperatures of the biogas can be attributed to the change in H2 O content caused by a better fuel-air mixture. It is also observed that adding H2 O into the biogas lowers the axial temperature levels. Highlights: Combustion of biogas fuels containing H2 0 have been modelled. The effect of H2 0 content in biogas on emissions has been investigated. A decrease in the H2 O content leads to a rise the flame temperature. The effect of O2 content in air on combustion has been predicted.